Stakeholder perceptions of IFRS utility - Benetti, Cristiane (2011)
The main objective of this study is to determine how individuals involved in the accounting process view the role of accounting information in an economic environment where capital markets are dominant. The study also attempts to determine whether International Financial Reporting Standards (IFRS) play a part in fulfilling this role. To this end, we compare the perceptions of financial officers, financial analysts and auditors from two distinctly market environments, using Europe as a proxy for a highly developed capital market environment and Brazil as a proxy for a less developed capital market environment. By means of a survey, we investigate whether producers of accounting data (financial officers), users of that data (financial analysts), and controllers of accounting information (auditors) share the same views on the usefulness and goals of the financial accounting process. Extending the study to several countries is a useful means for determining whether and how the economic environment affects the respondents\' views of accounting information. We use descriptive statistics, univariate tests and multiple correspondence analyses (MCA) to analyze the responses to our multiple-choice questions. Results suggest that respondents\' activity has less influence on their answers than the country where they are located.